6, 7, 3′, 4′-Tetrahydroxyisoflavone improves the survival of whole-body-irradiated mice via restoration of hematopoietic function. (3rd August 2017) - Liu, Cong; Liu, Jing; Hao, Yuhui; Gu, Ying; Yang, Zhangyou; Li, Hong; Li, Rong
Abstract: Purpose: 6, 7, 3′, 4′-tetrahydroxyisoflavone (T3) is a novel chemically synthesized compound reported in our previous study. This study was designed to explore the radioprotective effect of T3, and if so, its potential mechanisms. Materials and methods: KunMing mice were exposed to various doses of γ irradiation (60 Co) after being treated with dimethyl sulfoxide (DMSO) or T3. Briefly, survival rate, dose reducing factor (DRF), body weight change (%), spleen index (SI) and thymus index (TI) of irradiated mice with or without different doses of T3 treatment were evaluated routinely. The hematopoietic function of bone marrow was emphatically investigated. In vitro experiments were performed to observe the protective effect of T3 on irradiated human lymphocyte AHH-1 cells by cell viability or flow cytometry (FCM) assays. Results: A single dose of subcutaneous administration of T3 significantly improved the survival rate, and enhanced the restoration of hematopoietic function in irradiated mice. T3 also decreased the apoptosis of irradiated AHH-1 cells in vitro. Conclusions: T3 protected mice against lethal γ irradiation-induced injury probably through the restoration of hematopoietic function. This implied that T3 could be further developed as a radioprotector.